Milk Caramel Candy Quality by Added Sugar and Red Ginger (Zingiber officinale var rubrum) - Wulandari, A. T. R; Malaka, R.; Maruddin, F. (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
Caramel candy or toffee is a confectionery product made from basic sugar, glucose syrup, milk, fat, and salt ingredients. Sugar plays a role in the formation of brown color and caramelization, while the addition of red ginger acts as a flavor enhancer for caramel candy. The reaction results in the production of melanoid and antioxidant compounds. It also affects the taste, texture, aroma, and appeal of caramel candy. This research aimed to analyze the effects of the use and interaction of sugar and red ginger on antioxidants, organoleptic tests, and color L*, as well as chemical (reducing sugar and water content) changes in caramel candy products. This research design used a completely randomized design with a factorial pattern, with factor A adding sugar (0, 5, 10, 15) %; factor B adding red ginger juice (0, 2, 4, 6) %. This research shows that sugar and ginger juice can increase the A* color value, ginger taste, caramel taste, color, ginger, and caramel aroma. Meanwhile, increasing sugar and ginger juice can reduce the L* color value, antioxidant activity, and water content. Adding 15% sugar and 4% red ginger juice is the best for making red ginger juice. Keywords: Milk caramel candy, red ginger juice, sugar, physicochemical quality